Brain-Inspired Computing 4th International Workshop, BrainComp 2019, Cetraro, Italy, July 15-19, 2019, Revised Selected Papers - Amunts, Katrin; Grandinetti, Lucio; Lippert, Thomas; Petkov, Nicolai (Lecture Notes in Computer Science; Theoretical Computer Science and General Issues, 2021)
This open access book constitutes revised selected papers from the 4th International Workshop on Brain-Inspired Computing, BrainComp 2019, held in Cetraro, Italy, in July 2019. The 11 papers presented in this volume were carefully reviewed and selected for inclusion in this book. They deal with research on brain atlasing, multi-scale models and simulation, HPC and data infra-structures for neuroscience as well as artificial and natural neural architectures.